Rising Political Consciousness: Transformational Learning in Malaysia - Mazalan Kamis; Mazanah Muhamad (Adult Education Research Conference, 2002)
The qualitative study on ten educated Malays with regard to the rising political consciousness indicated their transformation is influenced by their culture. Political event can trigger a perspective transformation if it was perceived as threatening to ones communal cultural identity. The findings suggest that cultural values and religious beliefs facilitate the perspective transformation.